Investigating Agrobacterium-Mediated Transformation of Verticillium albo-atrum on Plant Surfaces - Knight, Claire J. (Public Library of Science, 2010)
BACKGROUND: Agrobacterium tumefaciens has long been known to transform plant tissue in nature as part of its infection process. This natural mechanism has been utilised over the last few decades in laboratories world wide to genetically manipulate many species of plants. More recently this technology has been successfully applied to non-plant organisms in the laboratory, including fungi, where the plant wound hormone acetosyringone, an inducer of transformation, is supplied exogenously. In the natural environment it is possible that Agrobacterium and fungi may encounter each other at plant wound sites, where acetosyringone would be present, raising the possibility of natural gene transfer from bacterium to fungus. METHODOLOGY/PRINCIPAL FINDINGS: We investigate this hypothesis through the development of experiments designed to replicate such a situation at a plant wound site. A. tumefaciens harbouring the plasmid pCAMDsRed was co-cultivated with the common plant pathogenic fungus Verticillium albo-atrum on a range of wounded plant tissues. Fungal transformants were obtained from co-cultivation on a range of plant tissue types, demonstrating that plant tissue provides sufficient vir gene inducers to allow A. tumefaciens to transform fungi in planta. CONCLUSIONS/SIGNIFICANCE: This work raises interesting questions about whether A. tumefaciens may be able to transform organisms other than plants in nature, or indeed should be considered during GM risk assessments, with further investigations required to determine whether this phenomenon has already occurred in nature.